Effect of statin use on oncologic outcomes in head and neck squamous cell carcinoma. Issue 8 (22nd June 2018) - Lebo, Nicole L.; Griffiths, Rebecca; Hall, Stephen; Dimitroulakos, Jim; Johnson‐Obaseki, Stephanie
Abstract: Background: Preclinical and early‐phase clinical studies have suggested an oncoprotective role of statins in head and neck squamous cell carcinoma (HNSCC). The purpose of this study was to determine whether incidental statin use in patients with human papillomavirus (HPV)‐negative HNSCC is predictive of improved oncologic outcomes. Methods: A retrospective cohort study of 1194 patients from the Ontario Cancer Registry diagnosed with HNSCC from 2007 to 2012 was performed using linked databases from the Institute for Clinical Evaluative Sciences. Overall survival (OS) and disease‐specific survival (DSS) were compared between patients taking statins and controls. Results: Patients with statin exposure demonstrated improved OS (hazard ratio [HR] 0.758; P = .0011; 95% confidence interval [CI] 0.642‐0.896), and DSS (HR 0.693; P = .0040; 95% CI 0.539‐0.889) compared with those not on statins at the time of diagnosis. Conclusion: Incidental statin use at the time of diagnosis of HPV‐negative squamous cell carcinoma (SCC) of the larynx, hypopharynx, and nasopharynx demonstrated improved OS and DSS.